OP0170 Infection Risk by Type and Treatment for Patients with Rheumatoid Arthritis (RA). (10th June 2014) - Michaud, K.; Pedro, S.; Mikuls, T.; Kalil, A.; Wolfe, F.
Abstract : Background: The specific impact of disease measures and current treatments on the risk of serious infections for patients with Rheumatoid Arthritis (RA) are still unknown. In addition, few have examined these risks by type and site of infections. Objectives: To assess the risk of serious infections by type and treatment in patients with RA compared to non-inflammatory rheumatic disease (NIRD) controls. Methods: Patients enrolled in a longitudinal observational study, the National Data Bank for Rheumatic Diseases, were followed from 1998 to 2013. Infections requiring intravenous antibiotics or hospitalization were validated from hospitalization records, physician reports and death records. Infections were categorized as opportunist, by cause (bacterial, viral or fungal) and by syndrome (pneumonia, CNS, abdominal, bone, urinary, skin, and sepsis/blood). Survival analysis methods (Cox regression, time to first infection using time-varying covariates and Andersen-Gill multiple failures model) were applied to identify age- and sex-adjusted risk factors. These included demographics, clinical status, disease severity and medications (prednisone, and for RA: methotrexate (MTX), anti-TNF (TNF) and other biologics (nTNF)). Significant factors were then selected in the multivariate models. Results: 20, 941 RA and 6300 NIRD patients contributed 125, 401 patient-years of exposure. Baseline characteristics by disease (RA:NIRD) were age (58:63 yrs), sex (78:80% female), HAQ (1.0: 0.9), comorbidities (1.7:1.8), and ever smoked (50:44%). The 2496 infections involved 1966 patients (1657:309). The Table shows the HRs for infections by type after adjusting for age, sex, smoking, education, comorbidity, pain, HAQ, and prednisone use. The impact of RA treatment group had similar adjustment. A significantly higher risk for all and bacterial infections were associated with RA. By site, only pneumonia, bone/joint, and sepsis seemed to differ in RA. None of the biologic classes appeared to be statistically associated with time to infection, both by type or site. Conclusions: RA patients have an increased risk of serious infection of any type and bacterial cause when compared with NIRD patients. Additional exposure will be necessary to further delineate the risk for infection type in RA patients by individual drugs. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3963